Exchange rate regime and stock market volatility / Noor Zahirah Mohd Sidek ... [et al.] - Mohd Sidek, Noor Zahirah; Abidin, Norridzwan; Umar, Azli (2007)
The choice of exchange rate regime and its possible impact on economic performance has recently become a new area of interest amongst both economists and policy makers. The study on the impact of financial performance, however, is still moderate, partly due to theoretical ambiguity and the definition of financial performance itself Hence, this study intends to fill this gap by focusing on the volatility of selected stock indices in Malaysia over the different regimes.